Resultant linear acceleration of an instrumented head form does not differ between junior and collegiate taekwondo athletes' kicks - David O'Sullivan; Gabriel P. Fife; Willy Pieter; Taehee Lim; Insik Shin (Elsevier, 2016)
Objective: The purpose of this study was to compare the effects of various taekwondo kicks and age (school level) in absolute terms and relative body mass on the resultant linear acceleration (RLA) of an instrumented head form. Methods: Forty-eight male (middle school: 16; high school: 16; university: 16) taekwondo athletes were recruited for this study. Subjects performed 10 turning, 10 jump spinning hook, and 10 jump back kicks on a Hybrid II head mounted on a height-adjustable frame. Results: A 2-way (School × Kick) MANOVA was used to determine the differences in RLA between schools (age groups) by type of kick. There was no univariate School main effect for absolute RLA (η2 = 0.06) and RLA relative to body mass (η2 = 0.06). No univariate Kick main effects were found for absolute (η2 = 0.06) and relative RLA (η2 = 0.06). Conclusion: It is of concern that RLA did not significantly differ between school levels, implying that young taekwondo athletes generate similar forces to their adult counterparts, possibly exposing young athletes to an increased risk for head injuries.